2006
DOI: 10.1111/j.1440-1819.2006.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and education on the Trail Making Test and determination of normative data for Japanese elderly people: The Tajiri Project

Abstract: The Trail Making Test (TMT) is a common two-part neuropsychological test, in which visuospatial ability (TMT-A) and executive function (TMT-B) are evaluated. Normative data for this test have not been reported for Japanese subjects; therefore, the purpose of the present paper was to investigate the effect of age and education on the TMT in 155 healthy elderly adults with clinical dementia rating 0 (healthy). The participants were classified into three groups based on age (70-74 years, 75-84 years and ≥85 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 29 publications
12
66
0
Order By: Relevance
“…Hashimoto R et al (2006) tried to investigate the effect of age and education on the TMT in 155 healthy elderly adults with clinical dementia rating 0 (healthy) [16]. They suggested in their study that the time to complete TMT-B is affected by educational level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashimoto R et al (2006) tried to investigate the effect of age and education on the TMT in 155 healthy elderly adults with clinical dementia rating 0 (healthy) [16]. They suggested in their study that the time to complete TMT-B is affected by educational level.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of 27 prospective cohort studies with at least one year of follow-up among healthy communitydwelling older adults found that executive dysfunction, a subtle cognitive deficit, was associated with an increased risk for any fall and falls associated with serious injury [16][17][18]. Similarly, early mobility decline, assessed as slowing of gait, has been found to co-exist or even precede the onset of clinically demonstrable cognitive decline in older adults [19].…”
Section: Discussionmentioning
confidence: 99%
“…Hamdan and Hamdan 24 examining the influence of age and EL on Trail (A and B) test performance in 318 healthy adults aged between 18 and 81 years, divided according to education, reported that the less educated group needed more time to complete the task suggesting that at least more than two years of formal education would be necessary for the test completion. Hashimoto et al 25 study with older people concluded that there is a need for at least six years of schooling to the test set. Also, Elst et al 26 evaluated the influence of age, gender and EL in the Stroop test in adults, divided into groups according to education, observing that the lower the EL, the worse the performance.…”
Section: Discussionmentioning
confidence: 99%
“…They were adapted to different cultures and languages: Arabic [10] [11], Chinese [12], Hebrew [13], Japanese [14], Italian [15], Indian [16].…”
Section: Other Versions Of the Trail Making Testmentioning
confidence: 99%